Promene seruma MMP-9, NSE, MPO nivoa i prognostičnih faktora uticaja kod pacijenata sa intrakranijalnom aneurijom koji su podvrgnuti interventnoj emboliziji u različitom tajmingu lečenja: Prognostic factors in aneurysm embolization - Wu, Chunmiao; Dong, Xingyu; Li, Qiang; Liu, Shengming; He, Yuhao; Zhang, Yang; Zhang, Sunfu (Journal of Medical Biochemistry, 2023)
Background: To analyzse the changes in serum levels of matrix metalloproteinase-9 (MMP-9), neuroenolase (NSE), myeloperoxidase (MPO) and prognostic factors in patients with intracranial aneurysm (IA) undergoing interventional embolization at different treatment times. Methods: A retrospective analysis was made of 200 IA patients admitted to our department from January 2018 to June 2021 was performed. All patients underwent interventional embolization. According to the timing of surgery, the patients were divided into an early group (n=120, onset to surgery ≤72 h) and a delayed group (n=80, onset to surgery >72 h). The effect of embolization, complications and neurological deficit scale (NDS) scores were compared between the two groups. Serum MMP-9, NSE and MPO levels were compared before and after surgery, and the prognosis of all patients within 2 years after surgery was assessed by the Glasgow outcome scale (GOS) and divided accordingly into the good prognosis group (n=147) and the poor prognosis group (n=53) accordingly, and the prognostic factors influencing the patients were analysed univariately and multifactorially.Results: After surgery, the rate of complete embolismwas higher in the early group than in the delayed group (P0.05). At 3d, 1 month, and 6 months after surgery, the NDS scores of patients in both groups were lower than those before surgery, and the within-group comparison of the NDS scores of patients in both groups at different time points was statistically significant (P